Implementations of Shariah Compliant Homestays in the Islamic Tourism Sector to Improve the Community Socioeconomics in Sabah - Muin, Suhailah Abdul; Abdullah, Mohd Nor Azan; Ramli, Issraq; Rahman, Ahmad Tarmizi Abdul; Samuni, Norcikeyonn (Jurnal Multidisiplin Madani, 2024)
In the development of the Islamic tourism sector, which is gaining more attention and high demand among pilgrims both from home and abroad, industry players are racing to provide a variety of tourism facilities that suit the wishes and needs of tourists, such as Muslim-friendly accommodation. However, to meet the needs of tourists to obtain sharia-compliant homestay accommodation, each homestay operator needs to study and implement the procedures or guidelines for sharia-compliant homestay accommodation that have been outlined. Thus, this study will examine the implementation of the Shariah-Compliant Homestay Model concept involving a total of 30 homestay entrepreneurs who are active in homestay business around Kota Kinabalu, Kundasang, and Semporna, Sabah. In addition, views on the issues and challenges they go through while operating homestay service operations are also highlighted. The homestay operators also gave suggestions to further improve the sharia-compliant homestay services that will be implemented. The results of the study found that the implementation of homestay services based on sharia compliance to improve the socioeconomics of the community, especially in Sabah, did not achieve total compliance